ANALYZING FACTORS THAT DRIVE CONSUMER PREFERENCES ON FRANCHISED COFFEE SHOPS IN MANADO - Mongkol, Clinton (FEB Universitas Sam Ratulangi Manado, 2016)
Coffee shop is currently a most rapid developing business in the world and become a famous trend in food service. Every individual have different type of preferences, so, the coffee shops should use a good strategy in estimating the cost needed and how to survive in this industry among any competitors. It is known that the majority of people in Manado are familiar with consuming coffee as the part of their daily life. This research analyzed the factors that drive consumer preferences on franchised coffee shops in Manado used Factor Analysis method with 100 respondents and incidental sampling used to as the sampling technique.There are two main findings in this research as the preferences of consumers of franchised coffee shops in Manado, which are: Layout and Service Quality & Ambience. The recommendations that can be drawn in this research, is the management of franchised coffee shops should improve the barista skill, make new design of shop, music playing must be up-to-date, employees should keep their good attitude, keep promoting, coffee shop must always clean, room fragrance should match the shops’ environment. Keywords: consumer preferences,analysis factor, franchise, coffee shop